The Frequency of Intermediate Alleles in Patients with Cerebellar Phenotypes - Elena Capacci; Silvia Bagnoli; Giulia Giacomucci; Costanza Maria Rapillo; Alessandra Govoni; Valentina Bessi; Cristina Polito; Irene Giotti; Alice Brogi; Elisabetta Pelo; Sandro Sorbi; Benedetta Nacmias; et al. (The Cerebellum, 2023)
Cerebellar syndromes are clinically and etiologically heterogeneous and can be classified as hereditary, neurodegenerative non-hereditary, or acquired. Few data are available on the frequency of each form in the clinical setting. Growing interest is emerging regarding the genetic forms caused by triplet repeat expansions. Alleles with repeat expansion lower than the pathological threshold, termed intermediate alleles (IAs), have been found to be associated with disease manifestation. In order to assess the relevance of IAs as a cause of cerebellar syndromes, we enrolled 66 unrelated Italian ataxic patients and described the distribution of the different etiology of their syndromes and the frequency of IAs. Each patient underwent complete clinical, hematological, and neurophysiological assessments, neuroimaging evaluations, and genetic tests for autosomal dominant cerebellar ataxia (SCA) and fragile X-associated tremor/ataxia syndrome (FXTAS). We identified the following diagnostic categories: 28% sporadic adult-onset ataxia, 18% cerebellar variant of multiple system atrophy, 9% acquired forms, 9% genetic forms with full-range expansion, and 12% cases with intermediate-range expansion. The IAs were six in the FMR1 gene, two in the gene responsible for SCA8, and one in the ATXN2 gene. The clinical phenotype of patients carrying the IAs resembles, in most of the cases, the one associated with full-range expansion. Our study provides an exhaustive description of the causes of cerebellar ataxia, estimating for the first time the frequency of IAs in SCAs- and FXTAS-associated genes. The high percentage of cases with IAs supports further screening among patients with cerebellar syndromes.